Proceedings of the 8th Annual Conference on Genetic and Evolutionary Computation 2006
DOI: 10.1145/1143997.1144180
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of how and why neutrality affects evolutionary search

Abstract: The effects of neutrality on evolutionary search have been considered in a number of interesting studies, the results of which, however, have been contradictory. Some researchers have found neutrality to be beneficial to aid evolution whereas others have argued that the presence of neutrality in the evolutionary process is useless. We believe that this confusion is due to several reasons: many studies have based their conclusions on performance statistics (e.g., on whether or not a system with neutrality could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…Using a simple set of experiments, recent analysis has demonstrated this benefit to be problem dependent [9]. Our results provide a more subtle picture.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Using a simple set of experiments, recent analysis has demonstrated this benefit to be problem dependent [9]. Our results provide a more subtle picture.…”
Section: Discussionmentioning
confidence: 56%
“…While some studies have found no benefit [2,3,4], others have claimed that neutrality provides a buffer against deleterious genetic perturbation [5,6] and reduces the risk of premature convergence through an expansion of the search space [7,8]. As argued in [9], the lack of consensus regarding the benefits of neutrality largely stem from the overly complex problems, representations, and search algorithms used in these analyses, which make it difficult to tease apart the effects of neutrality from other confounding factors. Further, neutrality is often artificially added to the problem representation and little attention is paid to how this alters the fitness landscape [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its proven success, it also suffers from some limitations and researchers have been interested in making GP more robust, or reliable, by studying various elements of the search process (e.g., neutrality [4], [8], [9], [21], locality [5], [6], [7], special representations [3]). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this is also true for evolutionary algorithms (EAs), where the search for better fitness guides the evolutionary process. Fitness is the core element in understanding EA dynamics, with a large amount of research devoted at describing, understanding and analyzing fitness functions [1] and fitness landscapes [2], [3]; such as work done on locality [4], [5] and neutrality [6], [7], [8]. Fitness-based algorithms have achieved impressive results in many domains, for instance just considering the genetic programming (GP) paradigm a long list of examples exist [9].…”
Section: Introductionmentioning
confidence: 99%